Evaluation of the influence of incorporation of coconut oil in Bacterial Cellulose Membranes (Research, Society and Development, 2021)
Bacterial cellulose is an extracellular nanofibrillar polysaccharide that can be produced by acetic bacteria. This biopolymer has excellent characteristics, including high crystallinity, atoxity, high purity, high tensile strength, high water retention capacity, biocompatibility and biodegradability. The addition of vegetable oil in the matrix of this biopolymer appears as a possibility to promote a decrease in crystallinity and expand its applications in the most diverse areas, mainly food and medical-hospital. In this work, the influence of the incorporation of percentages of 0, 5 and 10% of coconut oil in Bacterial Cellulose (CB) membranes was evaluated. The membranes were characterized by the technique of Infrared Spectroscopy (FTIR), X-Ray Diffractometry (DRX) and Thermogravimetric Analysis (TGA). Through the FTIR technique, coconut oil was incorporated into the structure of CB membranes. Through XRD analysis it was noticed that the membranes added with coconut oil showed a reduction in the degree of crystallinity when compared to pure cellulose. Through the TGA technique it was found that the addition of coconut oil increased the thermal stability of the membranes, referring to the beginning of degradation of the biopolymer. Finally, it is understood that the membranes produced are a promising material in the packaging area due to the characteristics added by coconut oil to pure CB.